Perinatal tuberculosis—An approach to an under-recognized diagnosis - H. Simon Schaaf; Adrie Bekker; Helena Rabie (Frontiers in Public Health, 2023)
Tuberculosis (TB) in young infants (<3 months of age), often referred to as perinatal TB, is underdiagnosed, leading to severe morbidity and high mortality. Perinatal TB includes both congenital and postnatal transmission of Mycobacterium tuberculosis. We aimed to increase an awareness of TB in neonates and young infants and to provide guidance on the assessment and management when in contact with mothers with TB during or soon after pregnancy. Approximately 217,000 pregnant women develop TB annually; if they are not diagnosed and treated during pregnancy, their infants are at high risk of adverse birth outcomes and TB disease. Although safe and effective antituberculosis treatment regimens are available during pregnancy, the diagnosis of TB is challenging. Infants born to mothers newly diagnosed with TB, not receiving any effective treatment or with cultures not yet negative, should be assessed for TB disease or M. tuberculosis infection. TB preventive therapy should be instituted if the infant is clinically well but exposed to TB, while prompt initiation of TB treatment is essential if TB disease is presumed. HIV status of mother and infant should be considered as this will affect the management. Further research is needed for the diagnosis and prevention of TB during pregnancy, an early diagnosis of TB in infants, and antituberculosis drug pharmacokinetics in young infants.